1917
DOI: 10.5962/bhl.title.22293
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance in the asexual reproduction of Centropyxis aculeata

Abstract: The present status of the pure line hypothesis Literature cited. Appendix-Soine important correlation tables. (3) Inheritance in the Asexual Reproduction of Centropyxis aculeata. (4) diverse strains, called "pure lines", "clones", or "biotypes", differing from each other, but each one constant and invariable in its c\"n hereditary constitution. This last idea, that every individual of any given clone is precisely the sane in its genetic make-up as any otVier individual of the same clone, is the basic idea of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1920
1920
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…On the other hand, Middleton (1915) in Stylonychia, Stout (1915) with Coleus, Jennings (1916) with Difflugia, Root (1918) in Centropyxis, and Hegner (1918and Hegner ( , 1919 with Arcella seem to have found genetic variation wherever they sought it. Stocking (1915), studying abnormahties in Paramecium, found that of 122 strains containing abnormal individuals, in which the character was clearly hereditary, 97 were persistently abnormal races, i. e., they presumably were not subject to genetic variation in this regard; and 25 strains were subject to genetic variation, i. e., selection was effective in 25 strains.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…On the other hand, Middleton (1915) in Stylonychia, Stout (1915) with Coleus, Jennings (1916) with Difflugia, Root (1918) in Centropyxis, and Hegner (1918and Hegner ( , 1919 with Arcella seem to have found genetic variation wherever they sought it. Stocking (1915), studying abnormahties in Paramecium, found that of 122 strains containing abnormal individuals, in which the character was clearly hereditary, 97 were persistently abnormal races, i. e., they presumably were not subject to genetic variation in this regard; and 25 strains were subject to genetic variation, i. e., selection was effective in 25 strains.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Sexual reproduction and recombination are necessary for selection in metazoans. In protozoa, however, some success has been obtained for selection of cytoplasmic traits without the use of sexual recombination (8,13). Selection for the abnormality in Tokophrya was tried but so far with no success; perhaps selection over many generations would yield more significant results.…”
Section: Discussionmentioning
confidence: 99%
“…castellanii to encyst. In these media there was an efflux of material from the cells which was independent of osmolarity but which was minimized by the addition of magnesi-HE investigation of encystment under defined conditions has been made possible by the isolation and growth of a number of soil amoebae in axenic culture, A further measure of control of encystment has been obtained by replacing the growth medium of the amoebae with a non-nutrient saline which lacks completely sources of carbon and nitrogen (4, 13). Previous work has yielded con-*This work was carried out during the tenure of a Science Research Council Studentship (A.J.G.).…”
mentioning
confidence: 99%
“…Additionally, the test may or may not be ornamented with spines of varying number and length. As noted by several authors, this broad generic description permits considerable latitude in the morphology of species that can be attributed to the genus (e.g., Leidy, 1879;Root, 1918;Deflandre, 1929;Medioli and Scott, 1983;Ogden, 1988;Wanner, 1999). Centropyxid species have mainly been distinguished by variation in test size and shape, aperture size and form, as well as the number and length of spines.…”
Section: Introductionmentioning
confidence: 99%